Infliximab-Induced Immune Thrombocytopenic Purpura in an Ulcerative Colitis Patient - Mark Lai; Timothy Phan; Ola Niewiadomski; Nik Ding (Case Reports in Gastroenterology)
Introduction: Ulcerative colitis is a chronic inflammatory disease affecting the colon. Anti-tumor necrosis factor-alpha drugs are a cornerstone of management in ulcerative colitis both in induction and maintenance of remission. Thrombocytopenia is a rare side effect of these drugs. Case Presentation: We present a case of infliximab-induced immune thrombocytopenic purpura in a 34-year-old female ulcerative colitis patient. Conclusion: Infliximab can be a cause of drug-induced immune-related thrombocytopenia and patient’s platelet counts should be regularly monitored. In patients with severe thrombocytopenia and having been recently commenced on infliximab, prompt referral to hematology specialty is essential.